Dose Distribution Three-Dimensional Conformal Radiation Therapy (3DCRT) With 2 And 4 Directions in Treatment Planning System for Cervical Cancer Cases (International Journal of Scientific Research in Science and Technology, 2024)
Cervical cancer which attacks the cervix is triggered by a virus called human papilloma virus (HPV). One effective treatment method for cervical cancer is external radiotherapy using a Linear Accelerator (Linac). This research aims to obtain radiation dose distribution by comparing the effectiveness of two treatment techniques cervical cancer, through Conformity Index (CI), Homogenity Index (HI), and radiation protection against Organ at Risk (OAR) in accordance with QUANTEC rules. The techniques used is Three Dimensional Conformal Radiation Therapy (3DCRT) with 2 directions of irradiation (anterior – posterior) and 4 directions of irradiation (box). Research data was obtained from 15 images of cervical cancer patients who have contoured by a Radiation Onkology Doctor at Indriati Hospital Solo Baru. From the result of the research, it can be said that the 3DCRT technique with 4 directions It can be seen from a higher Conformity Index (CI) value indicating a better level of conformity, and a lower Homogenity Index (HI) value indicating a higher level of homogenity. In addition, the 3DCRT technique with 4 directions of irradiation is also considered more effective in protecting OAR compared to 2 directions of irradiation.